24+4(7x-9)=7(5x+8)
24 + 4(7x + -9) = 7(5x + 8)
24 + 4(-9 + 7x) = 7(5x + 8)
24 + (-9 * 4 + 7x * 4) = 7(5x + 8)
24 + (-36 + 28x) = 7(5x + 8)
24 + -36 = -12 -12 + 28x = 7(5x + 8)
-12 + 28x = 7(8 + 5x)
-12 + 28x = (8 * 7 + 5x * 7)
-12 + 28x = (56 + 35x)
-12 + 28x = 56 + 35x
-12 + 28x + -35x = 56 + 35x + -35x
28x + -35x = -7x
-12 + -7x = 56 + 35x + -35x
35x + -35x = 0
-12 + -7x = 56 + 0
-12 + -7x = 56
-12 + 12 + -7x = 56 + 12
-12 + 12 = 0
0 + -7x = 56 + 12
-7x = 56 + 12
56 + 12 = 68
-7x = 68
x = -9.71